2010
DOI: 10.1037/a0018877
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal predictors of reading and math trajectories through middle school for African American versus Caucasian students across two samples.

Abstract: This study's primary purpose was to examine the relative contribution of social-behavioral predictors to reading and math skills. The study expands on Duncan et al.'s (2007) work by using longitudinal methodology from the National Institute of Child Health and Human Development's Study of Child Care and Youth Development (SECCYD) and the Early Childhood Longitudinal Study, Kindergarten Class of 1998-1999 (ECLS-K) databases, and by focusing on potential differences in patterns of early predictors of later readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 50 publications
4
61
0
2
Order By: Relevance
“…Only children's grade was significantly predictive of variance in children's Calculation subtest. These findings follow with past research that has identified links between early literacy skills and early mathematics development (Duncan et al, 2007;Hecht et al, 2001;Hooper et al, 2010;Lee et al, 2009;Matthews et al, 2009) and fill a gap in this research domain by identifying the unique relations between early literacy and early numeracy skills.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Only children's grade was significantly predictive of variance in children's Calculation subtest. These findings follow with past research that has identified links between early literacy skills and early mathematics development (Duncan et al, 2007;Hecht et al, 2001;Hooper et al, 2010;Lee et al, 2009;Matthews et al, 2009) and fill a gap in this research domain by identifying the unique relations between early literacy and early numeracy skills.…”
Section: Discussionsupporting
confidence: 54%
“…The two central domains of children's early academic achievement are reading and mathematics. These two domains not only are important individually but also are necessary for the reading skills are predictive of each other over time, even as late as middle school and high school (Hooper, Roberts, Sideris, Burchinal, & Zeisel, 2010). Potential explanations for the significant relations between these domains include genetic, cognitive, and environmental links (Farrington-Flint, Vanuxem-Cotterill, & Stiller, 2009;Gathercole, Pickering, Knight, & Stegmann, 2004;Hart, Petrill, Thompson, & Plomin, 2009;Rohde & Thompson, 2007;Spinath, Spinath, Harlaar, & Plomin, 2006;Swanson & Beebe-Frankenberger, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is growing consensus concerning which cognitive and linguistic processes are important to early math development (and math disabilities) (e.g., Fletcher, Lyon, Fuchs, & Barnes, 2006;Geary, 1994). Although intelligence is known to be related to the development of cognitive, linguistic, and mathematics skills (Geary, 1993(Geary, , 2007Noël, 2009;Primi, Ferrão, & Almeida, 2010;Stock et al, 2010), recent research suggests that vocabulary is involved in solving many different types of math problems (Foster, Sevcik, Romski, & Morris, 2014;Hooper, Roberts, Sideris, Burchinal, & Zeisel, 2010;LeFevre et al, 2010;Praet, Titeca, Ceulemans, & Desoete, 2013). Evidence also indicates that phonological processing abilities (PPAs) are related to children's early math achievement (Baddeley, 1986;Bull & Johnston, 1997;Clarke & Shinn, 2004;Dehaene, 1992;Dehaene, Piazza, Pinel, & Cohen, 2003;Geary, Hoard, Byrd-Craven, Nugent, & Numtee, 2007;Hecht, Torgesen, Wagner, & Rashotte, 2001;Vukovic, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Taken together, these studies provided empirical evidence for the pivotal role of young children's phonological awareness skills in the acquisition and further development of mathematical competencies. Although far less studied than young children's phonological awareness skills, oral language also proves positively and predictively related to children's mathematical development (Hooper, Roberts, Sideris, Burchinal, & Zeisel, 2010;Romano, Babchishin, Pagani, & Kohen, 2010;Toll & Van Luit, 2014). A limited number of investigations on young children's print knowledge and mathematics, indicated that the former (linguistic) skill is correlates with and even predicts the latter (mathematical) competencies (Matthews, Ponitz, & Morrison, 2009;Piasta, Purpura, & Wagner, 2010;Purpura et al, 2011).…”
Section: Early Mathematical Abilities In Relation To Young Children'smentioning
confidence: 99%